A Pedagogical Note: Use of Telepractice to Link Student Clinicians to Diverse Populations - Stacy Gallese Cassel; Amy J. Hadley (International Journal of Telerehabilitation)
Telepractice is the application of telecommunications technology to the delivery of telehealth services via the online connection of clinicians, clients, and patients for assessment, intervention, or consultation.  This article describes a pilot project in which speech-language pathology students in a university training program gained experience in working with culturally diverse preschool students using telepractice technology. The preschool students benefited by making gains in communication skills, while the university students acquired competency in the use of telepractice and in working with children whose cultural and linguistic backgrounds were outside of their experience.  To assess the training experience, a Likert-scale survey administered to student clinicians revealed a high degree of satisfaction and improved familiarity with the use of telepractice, and an increased comfort level working with multi-cultural populations.